Gabapentin prevalence: clinical and forensic experience in St. Louis, Missouri, USA - Sarah B. Riley; Kelsie Garbutt; Chelsea Crow; T. Scott Isbell; Anthony J. Scalzo (Oxford University Press, 2021)
Gabapentin (Neurontin) is an anti-epileptic drug that has had wide off-label prescription use since market release due to presumed negligible abuse potential. However, trends in drug misuse have demonstrated that gabapentin misuse is occurring, particularly in those with a history of opioid misuse. This is concerning, because although gabapentin has no direct ligand activity at opioid receptors, it does potentiate the analgesic effect of opioids, and concurrent use of gabapentin and opioids may increase the risk of respiratory depressive effects of opioids. This study investigates the incidence of gabapentin detected in urine samples collected for clinical drug screening purposes in a local hospital emergency department and in postmortem samples submitted by medical examiners in the St. Louis metropolitan area. The prevalence of gabapentin and co-detected drugs in both populations is contrasted, compared, and discussed. This study found that 30% of urine samples collected from patients with suspected drug intoxication presenting to SSM Health Saint Louis University Hospital, a quaternary care medical center, were positive for gabapentin, and nearly two thirds of those were also positive for oxycodone. Over a 6-month period, the incidence of gabapentin positive postmortem cases increased from 18% to 20%. Nearly all gabapentin positive postmortem cases were also positive for an opioid, the most significant being fentanyl, suggesting that gabapentin misuse may be due to its potentiating effect of opioid drug action. This study also highlights the limited utility of immunoassay-based urine drug screens.